Michał Wasiucionek, Înalta Poartă şi Ţările Române. Rivalităţi şi alianţe în secolul al XVII-lea [The Sublime Porte and the Romanian Principalities. Rivalries and Alliances in the 17th Century], transl. Lia Decei (București: Humanitas, 2024), 360 pages - OLARU, Vasile Mihai (Studia Universitatis Babeș-Bolyai Historia, 2025)
Despite having been largely overlooked in Romanian historiography, this book[1] attempts to rethink “the political dynamics between the Sublime Porte, Poland–Lithuania and the Danubian principalities during the seventeenth century” (p. 8). The book's core tenet is that cross-border patron-client networks, rather than states and their formal institutions, were the main actors in the political life of seventeenth-century Eastern and Southeastern Europe. Accordingly, various episodes and processes are better understood through the lens of factional politics, rather than as relations – peaceful or conflictual – between states. Moreover, the author's argument amounts to a paradigm shift in how we conceptualize the relationship between the principalities of Wallachia and Moldavia, on the one hand, and the Ottoman Empire, on the other. [1] Original edition: The Ottomans and Eastern Europe: Borders and Political Patronage in the Early Modern World, (London, New York: I.B. Tauris, 2019). Although this is a review of the Romanian edition of the book, I use the English original when quoting directly or referring to the author's technical terms.